2020
DOI: 10.1002/hep.30917
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic Astrocyte‐Derived Neurotrophic Factor Inhibits Liver Cancer Through Small Ubiquitin‐Related Modifier (SUMO)ylation‐Related Suppression of NF‐κB/Snail Signaling Pathway and Epithelial‐Mesenchymal Transition

Abstract: Background and Aims Endoplasmic reticulum (ER) stress is associated with liver inflammation and hepatocellular carcinoma (HCC). However, how ER stress links inflammation and HCC remains obscure. Mesencephalic astrocyte‐derived neurotrophic factor (MANF) is an ER stress‐inducible secretion protein that inhibits inflammation by interacting with the key subunit of nuclear factor kappa light chain enhancer of activated B cells (NF‐κB) p65. We hypothesized that MANF may play a key role in linking ER stress and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 39 publications
1
68
0
Order By: Relevance
“…The endogenous NO produced by tumor cells and tumor vascular endothelial cells plays an important role in promoting tumor angiogenesis and ensuring the maximum blood supply of tumors. Tumor angiogenesis is the basis of tumor growth and metastasis [88].…”
Section: Oxidative Stress and Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The endogenous NO produced by tumor cells and tumor vascular endothelial cells plays an important role in promoting tumor angiogenesis and ensuring the maximum blood supply of tumors. Tumor angiogenesis is the basis of tumor growth and metastasis [88].…”
Section: Oxidative Stress and Tumorsmentioning
confidence: 99%
“…The transcription factors NF-κB and STAT3 are involved in inflammation and tumorigenesis and regulate cell survival, growth, and proliferation [97]. Many cytokines involved in the inflammatory response, such as TNF and IL-1, are involved in the activation of the NF-κB signaling pathway [88]. Activation of the STAT3 pathway also primarily depends on the corresponding inflammatory cytokines, such as IL-6, IL-10, and VEGF [98,99].…”
Section: Oxidative Stress and Tumorsmentioning
confidence: 99%
“…A lot of studies have revealed that NF-κB and p65 phosphorylation play a key role in the EMT process [17][18][19][20]. In order to clarify the effect of PA3611 on the expression of p65 p-p65 and EMT process, 16HBE and RTE cells were treated with PBS (negative control), TGF-β1 (2ng/ mL positive control), PA3611 (30ug/mL), and PA3611 (30ug/mL) + TGF-β1 neutralizing antibody (10μg/mL) for 24 hs, the results indicated that: TGF-β1 and PA3611 increased the expression of p-p65, α-SMA and Vimentin and decreased the expression of E-cadherin and Zo-1 obviously compared with PBS group, while PA3611 + TGF-β1 neutralizing antibody signi cantly decreased the expression of p-p65, α-SMA and Vimentin, and promoted the expression of E-cadherin and Zo-1, of which the change trend was similar to that in PBS group (Fig 2 B-H).…”
Section: Pa3611 Stimulation Of Tgf-β1 Production Is Accompanied By Prmentioning
confidence: 99%
“…Recently, we reported that in comparison to liver cancer tissues in HCC patients, the MANF level was higher in the adjacent noncancer tissues of the same patient. MANF also acts as a cancer suppressor by inhibiting the NF- κ B/Snail signal pathway in HCC progression [ 16 ]. However, how hepatic MANF expression is affected by alcohol exposure and whether MANF can contribute to the hepatocyte survival in alcohol-induced liver injury remain unknown.…”
Section: Introductionmentioning
confidence: 99%